2022
DOI: 10.3389/fphar.2022.954596
|View full text |Cite
|
Sign up to set email alerts
|

Associations of HLA-A and HLA-B with vancomycin-induced drug reaction with eosinophilia and systemic symptoms in the Han-Chinese population

Abstract: Vancomycin is a commonly used antibiotic; however, it can cause life-threatening severe cutaneous adverse reactions, such as drug reaction with eosinophilia and systemic symptoms (DRESS). A previous study has reported a strong association between HLA-A*32:01 and vancomycin-induced DRESS in European ethnicity. Herein, we aim to investigate the genetic predisposition of vancomycin-induced DRESS in the Han-Chinese population. In this study, we enrolled a total of 26 patients with vancomycin-induced DRESS, 1,616 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“… Bellon et al (2022) also revealed the association between HLA-A*32:01 and vancomycin-induced DRESS in Spanish population. Recently, we reported the association between HLA-A*32:01, HLA-B*07:05, HLA-B:40:06, HLA-B*67:01 and vancomycin-induced DRESS in Taiwanese population ( Wang et al, 2022c ). However, Lee et al (2022) reported that there is no association between HLA-A*32:01 and vancomycin-induced SCARs in Korean population according to clinical data from Seoul National University Hospital.…”
Section: Hla Susceptibility To Drug-induced Scarmentioning
confidence: 99%
“… Bellon et al (2022) also revealed the association between HLA-A*32:01 and vancomycin-induced DRESS in Spanish population. Recently, we reported the association between HLA-A*32:01, HLA-B*07:05, HLA-B:40:06, HLA-B*67:01 and vancomycin-induced DRESS in Taiwanese population ( Wang et al, 2022c ). However, Lee et al (2022) reported that there is no association between HLA-A*32:01 and vancomycin-induced SCARs in Korean population according to clinical data from Seoul National University Hospital.…”
Section: Hla Susceptibility To Drug-induced Scarmentioning
confidence: 99%
“…HLA-A*32:01 has also been associated with vancomycin DRESS in Asian populations; however, it is potentially not the only association with this allele less commonly represented. In addition, since vancomycin DRESS has a median latency of 3 weeks countries that step-down earlier to oral therapy experience less vancomycin DRESS in their populations 89. F I G U R E 1 Phenotypes, endotypes, and biomarkers in drug hypersensitivity.…”
mentioning
confidence: 99%